2016
DOI: 10.1063/1.4942979
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric barrier discharge actuator for vehicle drag reduction at highway speeds

Abstract: We propose and demonstrate reduction of aerodynamic drag for a realistic geometry at highway speeds using serpentine dielectric barrier discharge actuators. A comparable linear plasma actuator fails to reduce the drag at these speeds. Experimental data collected for linear and serpentine plasma actuators under quiescent operating conditions show that the serpentine design has profound effect on near wall flow structure and resulting drag. For certain actuator arrangement, the measured drag reduced by over 14% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…The truck model was attached to an active flow control device to modify the flow of air in the regions covering the front and rear wheels and the underbody of truck. The Active Flow Control device employed for investigation was a Single Dielectric Barrier Discharge Plasma Actuator (SDBD) Roy, et al (2016) implanted on the side of the truck which runs vertically as two individual units on both the sides, intended to perform the function of side skirt. The The SDBD is embodied of a dielectric medium with two electrodes etched on the top and bottom layer of the dielectric of which the bottom electrode should be an encapsulated with a kapton tape and the top one as an exposed electrode.…”
Section: 3 Design Of Active Side Skirtmentioning
confidence: 99%
See 1 more Smart Citation
“…The truck model was attached to an active flow control device to modify the flow of air in the regions covering the front and rear wheels and the underbody of truck. The Active Flow Control device employed for investigation was a Single Dielectric Barrier Discharge Plasma Actuator (SDBD) Roy, et al (2016) implanted on the side of the truck which runs vertically as two individual units on both the sides, intended to perform the function of side skirt. The The SDBD is embodied of a dielectric medium with two electrodes etched on the top and bottom layer of the dielectric of which the bottom electrode should be an encapsulated with a kapton tape and the top one as an exposed electrode.…”
Section: 3 Design Of Active Side Skirtmentioning
confidence: 99%
“…Moreau (2007) had reported that the electric winds created by the plasma formation on the DBD plasma actuator directed span wise manipulated the surrounding air with less input power and suggested that plasma should act at the right time and location. Roy et al (2016) demonstrated the, use of plasma actuator for reducing the base drag and achieved 10 % reduction in aerodynamic drag at speed of 31.21 m/s for a scaled tractor-trailer model, but the power needed to actuate the plasma actuator was 4.5 times more than power saved, so there arises a need to design an efficient plasma actuator which is on par with the passive flow control devices with the aim of reducing drag. The dielectric barrier discharges based plasma actuators that had been created are with AC HV supply and had been presented by (Yokoyama et al 1990 andFridman et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on numerical modeling of DBD plasma actuators present the effects of DBD actuators on the flow over geometries such as an airfoil and a backward step . The analysis of quiescent flow and with freestream flow presents the charge density and discharge current variation along with instantaneous charge and velocity distribution plots.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on numerical modeling of DBD plasma actuators present the effects of DBD actuators on the flow over geometries such as an airfoil and a backward step. 1,3,16,22 The analysis of quiescent flow 23 and with freestream flow 18 presents the charge density and discharge current variation along with instantaneous charge and velocity distribution plots. An experimental analysis of quiescent flow and flow control with plasma actuators, for an annular electrode, 24 was presented including velocity profiles of freestream flow along with the evolution of quiescent flow.…”
mentioning
confidence: 99%
“…Dielectric barrier discharge (DBD) plasma actuators are promising devices for flow control that can be applied to a number of scenarios: flow separation postponement, turbulence augmentation, drag reduction, and lift enhancement. Many numerical and experimental investigations have shown the effectiveness of DBD plasma actuators for engineering applications; such as film cooling [1,2], aircraft wing [3][4][5], and ground vehicles [6,7]. The experiment of Benard et al [8] demonstrated that the DBD plasma actuator placed on a NACA0015 aircraft wing delays the onset of stall by one or two degrees and achieved approximately 30% drag reduction at a 15 degree incidence.…”
Section: Introductionmentioning
confidence: 99%